Automatic Packaging Machine And Cooling & Strainer Machine For Production Of Crunchy Nuts - Katijan, Adnan; Parnon, Mohamad Afiq Amiruddin; Nordin, Abd Khahar; Abduk Katif, Mohd Faruq; Zahmani, Qamar Fairuz; Aziz, Azwan (UTeM, 2019)
This PPRN project is a kind of grant from MOHE that helps small and medium-sized industries improve their quality and production systems. As stated by the East Rich Enterprise in the proposal, there are three main concerns about the process. First, the company has problem with inconsistent nitrogen gas content in the packaging of their product. This is because the nitrogen gas content was estimated and controlled manually by the worker by holding each product before sealing. Second problem is the weighing system. The weighing process for the product is done manually which is time consuming and uses many manpower. Third, the fried peanuts are oily and require some time to cool down (1 hour) before it is packaged. The excess oil can cause the product to become rancid (short shelf life). The fabricated machines can increase production of crunchy nuts by more than 20%. Oily peanuts have been solved and no more leakage found in the packaging seal.